A review of the genus Trichogorgia (Cnidaria, Octocorallia), including descriptions of new species - Cordeiro, Ralf T. S. (Zootaxa, 2019)
The genus Trichogorgia (Cnidaria: Octocorallia) is composed of mesophotic gorgonians, and has been traditionally included in the Family Chrysogorgiidae. The family is polyphyletic and in need of generic morphological reassessments. Herein, two new species of that genus are described, based on material deposited in the National Museum of Natural History—Smithsonian Institution. Additionally, we provide a taxonomic key to all species of Trichogorgia, also briefly discussing important characters of the group and closely related taxa.